The molecular basis of phosphite and hypophosphite recognition by ABC-transporters - Claudine Bisson (Nature Portfolio, 2017)
Some bacteria can use inorganic phosphite and hypophosphite as sources of inorganic phosphorus. Here, the authors report crystal structures of the periplasmic proteins that bind these reduced phosphorus species and show that a P-H…π interaction between the ligand and binding site determines their specificity.